Glioma risk associated with extent of estimated European genetic ancestry in African Americans and Hispanics. Issue 3 (22nd April 2019) - Ostrom, Quinn T.; Egan, Kathleen M.; Nabors, L. Burt; Gerke, Travis; Thompson, Reid C.; Olson, Jeffrey J.; LaRocca, Renato; Chowdhary, Sajeel; Eckel‐Passow, Jeanette E.; Armstrong, Georgina; Wiencke, John K.; Bernstein, Jonine L.; et al.
Abstract : Glioma incidence is highest in non‐Hispanic Whites, and to date, glioma genome‐wide association studies (GWAS) to date have only included European ancestry (EA) populations. African Americans and Hispanics in the US have varying proportions of EA, African (AA) and Native American ancestries (NAA). It is unknown if identified GWAS loci or increased EA is associated with increased glioma risk. We assessed whether EA was associated with glioma in African Americans and Hispanics. Data were obtained for 832 cases and 675 controls from the Glioma International Case–Control Study and GliomaSE Case–Control Study previously estimated to have <80% EA, or self‐identify as non‐White. We estimated global and local ancestry using fastStructure and RFMix, respectively, using 1, 000 genomes project reference populations. Within groups with ≥40% AA (AFR≥0.4 ), and ≥15% NAA (AMR≥0.15 ), genome‐wide association between local EA and glioma was evaluated using logistic regression conditioned on global EA for all gliomas. We identified two regions (7q21.11, p  = 6.36 × 10 −4 ; 11p11.12, p  = 7.0 × 10 −4 ) associated with increased EA, and one associated with decreased EA (20p12.13, p  = 0.0026) in AFR≥0.4 . In addition, we identified a peak at rs1620291 ( p  = 4.36 × 10 −6 ) in 7q21.3. Among AMR≥0.15, we found an association between increased EA in one region (12q24.21, p  = 8.38 × 10 −4 ), and decreased EA in two regions (8q24.21, p  = 0. 0010; 20q13.33, p  = 6.36 × 10 −4 ). No other significant associations were identified. This analysis identified an association between glioma and two regions previously identified in EA populations (8q24.21, 20q13.33) and four novel regions (7q21.11, 11p11.12, 12q24.21 and 20p12.13). The identifications of novel association with EA suggest regions to target for future genetic association studies. Abstract : What's new? Glioma is rare in non‐White populations, and most glioma genome‐wide association studies have included only primarily European ancestry populations. Here, the authors assess whether variation in European ancestry is associated with glioma risk in populations with a combination of European, African and Native American ancestry. Based on African American and Hispanic cases from two large glioma case–control studies, this analysis shows that increased European ancestry in admixed populations may be associated with increased glioma risk. The associations between glioma and two chromosomal regions previously identified in European ancestry populations, and four novel regions, may guide future studies.